Strategic Business Plan of Sayang Holidays USA Travel Agency - Handayani, Trustorini; Murugesu, Karina Devi; Novianti, Windi; Iffan*, Muhammad; Santy, Raeni Dwi (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2022)
The development of tourists and tourism is going very fast which requires travel agencies to make adjustments and innovations. Sayang Holidays is a travel agency operating in California, San Francisco, USA. This study was conducted to excavate the feasibility of Sayang Holidays as a business entity engaged in the tourism sector. The method used is the Miles and Huberman model which divides into four stages, namely data collection, data reduction, data display, and decision making. From this study, it was found that Sayang Holidays is relevant and feasible in becoming a competitive travel agency in San Fransisco. The measurement was conducted from the marketing, human resource, financial ability, and operational aspects. It is hoped that this research can be useful for furthering the development of the business. Keywords: Travel Agency; Finance; Feasibility Study; Business Plan; Tourism Perkembangan wisatawan dan pariwisata yang berlangsung sangat cepat menuntut biro perjalanan untuk melakukan penyesuaian dan inovasi. Sayang Holidays adalah agen perjalanan yang beroperasi di California, San Francisco, AS. Kajian ini dilakukan untuk menggali kelayakan Sayang Holidays sebagai badan usaha yang bergerak di bidang pariwisata. Metode yang digunakan adalah model Miles dan Huberman yang terbagi menjadi empat tahapan yaitu pengumpulan data, reduksi data, display data, dan pengambilan keputusan. Dari penelitian ini ditemukan bahwa Sayang Holidays relevan dan layak untuk menjadi agen perjalanan yang kompetitif di San Fransisco. Pengukuran dilakukan dari aspek pemasaran, sumber daya manusia, kemampuan finansial, dan operasional. diharapkan penelitian ini dapat bermanfaat untuk pengembangan usaha selanjutnya. Kata Kunci: Agen Perjalanan; Keuangan; Studi Kelayakan; Rencana Bisnis; Pariwisata